USULAN PERBAIKAN PERENCANAAN PERSEDIAAN BAHAN PAKAN KONSENTRAT HEWAN TERNAK SAPI MENGGUNAKAN METODE LOT FOR LOT (LFL) LEAST UNIT COST (LUC) DAN LEAST TOTAL COST (LTC) PADA UD. SADEWA FARM - Pratama, Ero Pandu Jaya; Mawadati, Argaditia; Susetyo, Joko (Prodi Teknik Industri, Universitas AKPRIND Indonesia, 2023)
UD. Sadewa Farm is a business engaged in animal husbandry and animal trading, especially cattle. After observing and interviewing, it was found that the problems that occurred at UD. Sadewa Farm, namely the planning of concentrate feed supplies that are not optimal, where there is often a shortage and excess of feed so that it can interfere with the process of raising cattle. This study aims to propose an improvement in optimal supply planning of concentrate feed ingredients using the Lot for Lot (LFL), Least Unit Cost (LUC) and Least Total Cost (LTC) methods. In addition, this study also aims to provide suggestions for improvements regarding planning for optimal concentrate feed supply control at UD Sadewa Farm. The use of cattle feed at UD Sadewa Farm uses Calfeed 131 Concentrate feed. In this study, three inventory planning methods were used, namely by using Lot for Lot (LFL), Least Unit Coast (LUC) and Least Total Cost (LTC) measurements. These three methods are used to overcome the excess and shortage of Calfeed 131 concentrate feed ingredients. Based on the results of the research that has been done, the Least Total Cost (LTC) method is the most optimal planning method used at UD Sadewa Farm. With the use of the Least Total Cost (LTC) method, there are 4 frequencies of concentrate feed purchases for one year with the first order being 278 sacks for the period January-March, 252 sacks April-June, 254 sacks for the July-September period, and 264 sacks for the October-December period with a total Total Cost IDR 1,024,054